ERP IMPLEMENTATION IN HIGHER EDUCATION: PRODUCTIVITY AND USER’S UNDERSTANDING OF ERP CONCEPTS - Iyengar, Nirmal; Iyengar, Madhu; Tripathi, Shailesh; Shakdwipee, Pushpkant (International Journal of Research -GRANTHAALAYAH, 2019)
Motivation/Background: The review of extant literature suggests that ERP Implementation in general and ERP post implementation scenario in particular, in higher education in Indian context appear to have been a less explored area. The review also shows that although two factors, namely, user’s understanding of ERP concepts and their productivity, appear to be important to the success of ERP during post implementation stage, there is a very little or no evidence of studies in this area. Motivated by the observation, this paper reports an empirical study on the association between the two factors, in ERP post-implementation stage, in higher education institutions, especially, in an Indian context. Method: The study employed a descriptive design to examine the research problem. A search of multiple journals was carried out using key words identified in an initial review of literature. Successive rounds of review of abstract of articles led to identification of a few studies, which were examined in details to identify the gaps. Subsequently, using a purposive sampling and a survey of target respondents, the primary data was collected and analysed. The hypothesis to address research problem were analysed and interpreted using chi square test of independence. Results: The most important finding of the study was lack of research focusing on relationship between two important factors impacting ERP post-implementation stage, in the chosen setting. The investigation showed that the two factors under study, were dependent on each other. Conclusion: The outcome of the analysis, besides contributing to the body of knowledge in the gap area, would also be of great use for going in depth on the influence of these factors during the ERP post-implementation stage, in higher education institutions, especially in the Indian context.